Hubungan Stres Kerja Dan Beban Kerja Dengan Gejala Psikosomatis Pada Karyawan PT. Putra Dermawan Pratama - Asti Aulia Agusting; Andi Rezki Amelia; Ikhram Hardi S; Nasruddin Syam; Septiyanti (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Psychosomatic disorders are physical complaints experienced by an individual without a definite cause, but rather stem from thoughts or emotions. According to WHO data, in the UK, the incidence of work-related stress is 1,380 cases per 100,000 workers. The purpose of this study was to determine the relationships among work stress, workload, and psychosomatic symptoms among employees in the BBG pit area of PT. Putra Dermawan Pratama. This was a quantitative study with a cross-sectional design. The sampling technique used was total sampling. The study population consisted of 55 employees of PT. PDP in the BBG pit area. Data were obtained using a questionnaire. The analytical methods used were univariate and bivariate analysis using the chi-square test. While the findings suggest an association between work stress, workload, and psychosomatic symptoms, potential confounding factors such as individual health status or external stressors were not controlled for, which should be considered when interpreting the results. Based on these findings, the author recommends that companies conduct regular health checks for employees to understand better and address these factors.